The Words of Imam Al-Tahawi - (died 321 AH) - May Allah have Mercy on him - in Proving Companionship in the Book Explanation of the Meanings of Athars (Islamic Sciences Journal, 2023)
Imam Al-Tahawi had extensive hadith efforts in al-jarh and modification, criticizing the hadith and weighing one side over another in the book “Explanation of the meanings of the traces.” One of these efforts is to prove the companionship of the narrators whom he narrated in the book “Explanation of the meanings of the traces.” Those words, I collected them and quoted the sayings of the imams of critics regarding these narrators to know what al-Tahawi added of his knowledge to prove the companionship of these narrators.
Keywords: His personal life, his scientific life, El-Tahawy said: Abu Bakra told us, El-Tahawy said on the authority of Urwah, El-Tahawy said: Yahya told us .